Reshaping Smiles: A Successful Clinical Case with Botulinum Toxin for Gummy Smile Reduction - Dall'Magro, Alessandra Kuhn (2024)
The use of botulinum toxin (BTX) represents an effective and safe approach in treating the gummy smile, reducing excessive gum exposure during smiling. This minimally invasive procedure can yield remarkable aesthetic results and contribute to an increase in the patient's self-confidence. The aim of this study is to report a clinical case of a female patient undergoing treatment to correct a gummy smile. The case study involves a 21-year-old patient with excessive gum exposure (5 mm when smiling) who sought dental treatment. The origin of her gummy smile was mixed, and the treatment involved the application of 6 units of BTX type A at three specific points on the face. No complications were observed during the three-month follow-up period. Based on the case report, it can be concluded that BTX application for gummy smile treatment proved to be effective, safe, and comfortable in terms of recovery. The BTX approach to correcting a gummy smile is considered safe and entails straightforward recovery, producing satisfactory results that contribute to the improvement of aesthetics and the patient's well-being.